(untitled) (Baltic Journal of Sport and Health Sciences, 2017)
Background. Performance indicators, which consist of a selection or combination of action variables, can be used to define performance in invasion games. These performance indicators should relate to successful performance. The same principles of match analysis can be used in all invasive games, and typical performance indicators can also be easily translated from one sport to another. The purpose of this study was to determine differences in situational efficiency parameters that differentiate ice hockey teams according to outcome. Sample of entities consisted of 15 games played on IIHF World Championship Division I B. Methods. Situational efficiency variables that affected final outcome were comprised of 11 parameters. Differences between successful and unsuccessful teams were detected using Mann-Whitney U-test for nonparametric variables. Significant value was set at p ≤ .05. Results. Results showed overall statistical differences in situational parameters between winner and defeated teams. The best variables that differed teams were assists and shots on goal (Z = 3.94, p >.000 and Z = –3.40, p > .001), while on the other hand saves by goalie (Z = 3.26, p > .001) represented defeated teams. Conclusion. On the basis of obtained results we suggest that winning teams had greater team play which leads to better passing play and shooting on goal. Keywords: team sport, notational analysis, final outcome